Selective Occlusal Features Of Primary Dentiton In Malay Children At A Centre In Sungai Buloh/ Fathinah Hanem Azamzaki ... [et al.] - Azamzaki, Fathinah Hanem; Baharuddin, Nurhanis; Tandon, Shobha; Venkiteswaran, Annapurny (Faculty of Dentistry, 2018)
Objectives:To determine the different occlusal characteristics in primary dentition of 3 to 6 year old Malay children and to create a preliminary database for future Malaysian studies as currently none of the studies has been conducted in Malaysian population regarding the occlusal features in primary dentition. Materials and method:The subjects were within the age ranging from 3 - 6 years old attending nurseries and kindergartens located within Sungai Buloh, Selangor. Sixty subjects were screened but only 47 fulfilled the criteria to be included in this study. Intra-oral examination was done to determine the terminal plane, canine relationship, overjet, overbite and primate space in the subjects. Results: Almost two thirds of the subjects (72.34%) presented with straight terminal plane. All but one subject were observed with Class I canine relationship. 61.7% subjects were with an ideal overjet and 53.19% of subjects had an ideal overbite. The mean value for primate space in the maxilla was 2.92mm and 1.60mm in the mandible. There was no significant difference between gender in all the parameters assessed. Conclusion: The results from the study shown that only few of the subjects had a tendency of malocclusion in their permanent dentition. However, a longitudinal study should be done to follow up their occlusal feature in the permanent dentition.